Uji Ekstrak Daun Pepaya (Carica Papaya) Terhadap Larva Plutella xylostella (Lepidoptera: Plutellidae) - Victor G Siahaya; Ria Y Rumthe (Agrologia, 2014)
Plutella xylostella L. (Lepidoptera: Plutellidae) is one of the major pests on chinese cabbage (Brassica pekinensis). It damage the  2-6 week old plants. Larvae damage  crops by biting, chewing and then eating the lower surface of the leaves. The leaves will become transparent white, severe damage leaves behind only leaf bone. Papaya leaf (Carica papaya) could be used as a pesticide for crops because it contains substances that can inhibit eating even to kill insects pests. The purpose of this study was to verify the efficacy of  the papaya leaf extract against Plutella xylostella. The study was conducted in the laboratory of Plant Pests Faculty of Agriculture, Pattimura University. The design used was a completely randomized design with four papaya leaf extract concentration at 3 instar larvae through the  contact and stomach poison test. Observations were made on the early symptoms of poisoning, the percentage of larval mortality, and further Plutella xylostella stadium. The results showed that the highest mortality in the treatment of stomach and contact poison was occured at a concentration of 40 g/100 ml of water by 100%, while the lowest mortality at a concentration of 10 g / 100 ml of water, respectively by 35% and 20%.